2015
DOI: 10.1038/cr.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation requires a DNMT1 ubiquitin interacting motif (UIM) and histone ubiquitination

Abstract: DNMT1 is recruited by PCNA and UHRF1 to maintain DNA methylation after replication. UHRF1 recognizes hemimethylated DNA substrates via the SRA domain, but also repressive H3K9me3 histone marks with its TTD. With systematic mutagenesis and functional assays, we could show that chromatin binding further involved UHRF1 PHD binding to unmodified H3R2. These complementation assays clearly demonstrated that the ubiquitin ligase activity of the UHRF1 RING domain is required for maintenance DNA methylation. Mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
245
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(257 citation statements)
references
References 78 publications
(130 reference statements)
11
245
0
1
Order By: Relevance
“…Maintenance appears to be predominantly accomplished by DNMT1, which localizes to replication foci 4 and exhibits 10-40 fold higher binding affinity and catalytic activity towards hemi-methylated DNA substrates 57 . DNMT1 is also recruited to nascent DNA by the essential cofactor UHRF1 (ubiquitin-like, with PHD and RING finger domains 1), which exhibits a high affinity for hemi-methylated DNA through its SRA domain 8,9 and ubiquitinates the histone H3 tail to facilitate DNMT1 recruitment 10 . DNMT1 activity is further directed to the replication fork through its interaction with the proliferating cell nuclear antigen (PCNA) DNA clamp 11 , and deletion of DNMT1s PCNA-binding domain has been reported to delay post replication remethylation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance appears to be predominantly accomplished by DNMT1, which localizes to replication foci 4 and exhibits 10-40 fold higher binding affinity and catalytic activity towards hemi-methylated DNA substrates 57 . DNMT1 is also recruited to nascent DNA by the essential cofactor UHRF1 (ubiquitin-like, with PHD and RING finger domains 1), which exhibits a high affinity for hemi-methylated DNA through its SRA domain 8,9 and ubiquitinates the histone H3 tail to facilitate DNMT1 recruitment 10 . DNMT1 activity is further directed to the replication fork through its interaction with the proliferating cell nuclear antigen (PCNA) DNA clamp 11 , and deletion of DNMT1s PCNA-binding domain has been reported to delay post replication remethylation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…35,36 RING domain-mediated ubiquitination of histone H3 provides the docking site for DNMT1 and cooperative binding between TTD, PHD and SRA domains is prerequisite for ubiquitination. 37,38 Ubiquitination of histones (H3K18/23) mediated by the RING domain targeted DNMT1 to its substrate by interacting with ubiquitin interacting motif (UIM) present in the targeting sequence of DNMT1 ( Figure 2). 38,39 The ability of UHRF1 to maintain the methylation status in neo-synthesized DNA strands during S phase has been explained on the basis of allosteric regulation which induces UHRF1 to adopt different conformational states.…”
Section: Uhrf1: the Facilitator Between Dna Methylation And Histone Mmentioning
confidence: 99%
“…UHRF1 binds hemimethylated DNA via its SET‐ and RING‐associated (SRA) domain and recruits DNA methyltransferase 1 (DNMT1) to methylate the newly synthesized strand. Meanwhile, UHRF1 also serves as a E3 ubiquitin‐protein ligase to promote ubiquitylation of histone H3 by its RING domain, which provides the docking site for DNMT1 19. Studies have shown that the UHRF1 protein is regulated at both transcriptional and post‐translational levels.…”
Section: Introductionmentioning
confidence: 99%